The Twig Wasp of Cork Oak - Its Biology and Control - BAILEY, STANLEY F.; STANGE, LIONEL A. (Journal of Economic Entomology, 1966)
Cork oak (Quercus suber L.), the principal source of commercial cork, was introduced to this country in 1858 from acorns sent from Spain. For Many years no pests were noted. In 191R the twig wasp Plagiotrochus suberi Weld, not described until 1926, was observed injuring the tree in California. It has since become a pest, particularly when the cork oak is planted as an ornamental or shade tree. The larvae feed within a jellylike matrix in the small twigs. The resulting dead twigs on the infested trees pn,- sent an unsightly, brushy appearance. The wasp has 1 generation a year. The agamic females emerge from the twigs via a small round hole in May. They are very weak fliers and remain close to the twigs on which they originated. Oviposition is in the twig growth of the previous year. The eggs hatch in late summer and the larvae develop slowly, pupating the following April. The insect has been found in Switzerland and Portugal (where it probably originated) only in the past few years. The time and manner of introduction into California are not known. In North America the wasp is found only in California. Only moderate control has been obtained with sprays of lindane and carbaryl directed against the adult stage. A European aphid, Myzocallis borneri Stroyan, is now a pest of the cork oak in California. This record is new. Other insect pests of the tree in this country are of very minor importance.
The following values have no corresponding Zotero field: label: California;Plagiotrochus suberi;cork oak;twig wasp (PG)
Keywords: California; Cork oak; Plagiotrochus suberi; twig wasp (PG)